2017
DOI: 10.1007/s13224-017-1067-3
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin D Status in Mothers and Their Newborns and Its Association with Pregnancy Outcomes: Experience from a Tertiary Care Center in Northern India

Abstract: This study showed a very high prevalence of hypovitaminosis D among pregnant women and excellent correlation between maternal and fetal 25(OH) D levels. Hypovitaminosis D was associated with preeclampsia, increased Cesarean rate, and low birth weight babies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
27
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(30 citation statements)
references
References 16 publications
3
27
0
Order By: Relevance
“…13 However, studies from North India have shown higher rates. 8,14 According to the study done by Arora et al, the prevalence was 95.5% and similar rate of 93.5% was reported by Sharma et al This is probably due to the difference in the amount of sunshine between the two parts of the country.…”
Section: Resultssupporting
confidence: 61%
See 1 more Smart Citation
“…13 However, studies from North India have shown higher rates. 8,14 According to the study done by Arora et al, the prevalence was 95.5% and similar rate of 93.5% was reported by Sharma et al This is probably due to the difference in the amount of sunshine between the two parts of the country.…”
Section: Resultssupporting
confidence: 61%
“…7 Prevalence of 95-97% has been reported in the studies done in North India. 8 Current guidelines from WHO does not recommend vitamin D supplementation to improve maternal and perinatal outcomes but suggest supplementation of 200 IU per day in those with documented vitamin D deficiency. 9 Aim was to estimate the prevalence of vitamin D deficiency in pregnant women and their infants in South India.…”
Section: Introductionmentioning
confidence: 99%
“…Several lines of evidence suggest that there is a strong association between maternal 25(OH)D levels during pregnancy and newborn 25(OH)D concentrations at birth or in the early neonatal period [238][239][240][241][242]. Novakovic et al reported that maternal circulating 25(OH)D levels were the most significant regulator of neonatal circulating vitamin D concentrations, even over the impact of genetic factors [243].…”
Section: The Association Of Maternal Vitamin D Status and Child Vitammentioning
confidence: 99%
“…Worldwide, pregnant women are reported to have inadequate 25‐hydroxyvitamin D [25(OH)D] levels . In India, the prevalence of maternal vitamin D deficiency is high , where 96% are reported to have 25(OH)D levels <20 ng/mL while 60% are reported to have <12 ng/mL levels . Recent studies indicate that maternal vitamin D deficiency is linked to pregnancy complications and adverse outcome like preeclampsia , preterm birth , and intrauterine growth restriction .…”
Section: Introductionmentioning
confidence: 99%